2020
DOI: 10.1016/j.neurobiolaging.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Does amnesia specifically predict Alzheimer’s pathology? A neuropathological study

Abstract: Amnesia is a key component of Alzheimer's disease (AD) and the most important feature of its clinical diagnosis but its specificity has recently been challenged. This study investigated the ability of amnesia to predict AD in a clinicopathological dementia series. Ninety-one patients to which free and cued verbal memory assessment was administered during early cognitive decline, were followed until autopsy. Patients' histological diagnoses were classified as pure-AD, mixed-AD and non-AD pathologies. Data-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…The BCSB displayed good diagnostic accuracy, thus corroborating previous results 11,12,13,30 . DR was the best BCSB subtest, in comparing AD and controls.…”
Section: Discussionsupporting
confidence: 89%
“…The BCSB displayed good diagnostic accuracy, thus corroborating previous results 11,12,13,30 . DR was the best BCSB subtest, in comparing AD and controls.…”
Section: Discussionsupporting
confidence: 89%
“…Memory loss, the cardinal symptom of AD, is also prevalent in other brain diseases, such as FTD, albeit with different underlying pathologies, while also a part of the normal aging process. Because of overlapping symptoms, memory impairment has proved to be unable to reliably distinguish AD from non-AD dementias [18,[20][21][22]50,51]. Recently, visuospatial dysfunction has emerged as a potential marker that can detect AD-even in its earliest stages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, memory loss has been assumed to be the most sensitive and specific clinical marker of the underlying AD pathology. Recent studies, however, have raised questions as to memory loss' specificity to AD [17][18][19][20][21][22]. Bertoux et al [18], in particular, tested the memory of 91 volunteer patients who were in the early stages of cognitive decline.…”
Section: Visuospatial Dysfunction As a Biomarker For Admentioning
confidence: 99%
See 1 more Smart Citation
“…58 Indeed, the classical concept of preservation of episodic memory in FTD 59 has been challenged by a series of cognitive, neuroimaging, and pathological investigations. [60][61][62] Here, none of the included studies indicated differences between PSP and bvFTD or PNFA in terms of episodic memory. However, individuals with PSP showed better verbal episodic memory scores than SD, which may be due to the specific and severe semantic deficit observed in SD patients.…”
Section: Discussionmentioning
confidence: 84%